Impact Of Peruvian Public Policies Implemented During The Coronavirus Pandemic - Neyra Colchado, Omar James (2025)
The Covid-19 Pandemic marks a milestone in contemporary world history, triggering the closure of borders, deterioration of the economy around the world, modification of the behaviors of millions of people, modification and suspension of education at different levels, collapse of health systems, confinement, increase in poverty,  Millions of deaths worldwide, definitely these and many other effects of covid, had and will have repercussions on the future. Governments in the search to mitigate the impact of the pandemic, adopted sanitary, political and economic measures, in this scenario Peru is a unique case in the world that was and is even the subject of analysis; because despite the speed of the health and economic measures implemented, they were not effective, which was observed in the high rate of deaths and high rate of infections, placing our country as the leader in the ranking of deaths per million inhabitants worldwide. With this analysis, It is intended to explain the impact of political decisions on health management during the covid-19 pandemic between 2020 and 2022 in Peru, with the aim of reflecting as part of society, understanding that this type of health policy decisions, which initially might seem the most suitable,  they are not necessarily; especially considering that political errors such as the absence of scientific and technical input when formulating strategies, the absence of a surveillance system, the lack of efficient diagnostic tools, the lack of a strategy for communication, limiting oneself to information through a paternalistic discourse to justify the measures and restrictions imposed. Is consider that these political decisions in health management require an analysis, given that our country with the initial conditions (precarious health system, high levels of corruption, labor informality, lower development of the economy, etc.) of similar characteristics to other countries in the region with respect to the management of the pandemic, obtained negative results,  suggesting that the implementation of these implemented policies was negative or even counterproductive in several situations.